Allergic bronchopulmonary fungal disease without clinical asthma. Issue 5 (May 1981) - Glancy, J J; Elder, J L; McAleer, R
Abstract : During a retrospective survey of patients with pulmonary shadows and blood eosinophilia between the years 1965 and 1980, 42 patients were found with allergic bronchopulmonary fungal disease. Eleven of these had no clinical evidence of asthma. Three of these 11 had hypersensitivity to fungi other than Aspergillus sp. In the absence of asthma there was some difficulty in making a diagnosis, particularly where collapse of the upper lobe occurred in middle-aged or elderly patients and bronchogenic carcinoma was presumed responsible. We suggest that the term allergic bronchopulmonary aspergillosis be replaced by allergic bronchopulmonary fungal disease, the diagnosis be considered in patients with lung disease and blood eosinophilia even in the absence of asthma, and a wider range of fungal allergens be used for skin and precipitin tests.